EVALUASI PELAYANAN PUBLIK DALAM PEMBUATAN SURAT PENGANTAR DI KELURAHAN SANGIANG JAYA KECAMATAN PERIUK KOTA TANGERANG - Yusuf, Azhar Maulana; Sugara, Asep; Setiadi, Iwan Kresna (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The world of service is inseparable from human life. Every human being even when still in the womb of his mother has received services in the form of nutritional intake and prayer, the next phase is after enough time to be born into the world he also gets service. The dimensions that will be used as guidelines for research instruments are according to Jafar, 2019. In the process of this research, the author uses qualitative methods, namely by collecting data through observation and interviews, The quality of service of Sangiang Jaya Village Office, Periuk District, Tangerang Municipality from the perspective of the community through the dimension of reliability is quite good. Meanwhile, through the dimension  of responsiveness as a whole, service reliability is mostly good and timely when the community needs it. Through  the assurance dimension, it is found that most employees have been good according to their abilities and do not compare with each other. Through the dimension of empathy regarding the attention of officials and employees to the community when served, it is found that overall they are always close to the community. The quality of service of Sangiang Jaya Village Office, Periuk District, Tangerang Municipality from through the dimension of direct evidence (tangibles) is said to be good enough but needs the addition of modern equipment